Mastering emotions : feelings, power, and slavery in the United States - Dwyer, Erin Austin (America in the nineteenth century., 2021)
Mastering Emotions examines the interactions between slaveholders and enslaved people, and between White people and free Black people, to expose how emotions such as love, terror, happiness, and trust functioned as social and economic capital for slaveholders and enslaved people alike.